Pengaruh Pad, Dana Perimbangan dan Belanja Modal Terhadap Kinerja Keuangan dan Ukuran Pemda Sebagai Moderasi Studi Kasus pada Pemerintah Kabupaten dan Kota di Provinsi Jawa Tengah Tahun 2021 Sampai dengan 2023 - Nur Aisyah; Sobrotul Imtikhanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze and empirically verify the influence of Local Revenue, Fiscal Equalization Funds, and Capital Expenditure on Local Government Financial Performance, as well as to examine the moderating effect of Local Government Size. The population in this study includes 29 districts and 6 cities in Central Java Province, with an analysis period of three years from 2021 to 2023. The data used were obtained from the Budget Implementation Reports and Balance Sheets of the regencies and cities in Central Java Province for the years 2021 to 2023. The analysis methods applied were Multiple Regression Analysis and Reduced Regression Analysis. The results of the study indicate that Local Government Revenue and Capital Expenditure have a partial influence on Financial Performance, while Fiscal Equalization Funds do not have an influence. Additionally, the Size of Local Government moderates the influence of Capital Expenditure on Financial Performance, but does not moderate the influence of Local Government Revenue on Financial Performance.